A Nonsense Variant of ZNF462 Gene Associated With Weiss–Kruszka Syndrome–Like Manifestations: A Case Study and Literature Review - Zhao, Shaozhi; Miao, Chen; Wang, Xiaolei; Lu, Yitong; Liu, Hongwei; Zhang, Xinwen (Frontiers in Genetics, 2022)
Objective: To determine the clinical and genetic characteristics of a child and his father with Weiss-Kruszka syndrome in pedigree analysis. Methods: The clinical data of the child and his father were collected. The genomic DNA of the patient and his relatives were extracted from their peripheral blood samples and subjected to Trio-whole exome sequencing (Trio-WES) and copy number variation analysis. Sanger sequencing was used to verify the potential variant. Results: The sequencing analysis identified a heterozygous nonsense variant c.6431C>A（p.Ser2144*）in the ZNF462 gene (NM_021224.6) in the child and his father whereas the locus in his asymptomatic mother, brother, and grandparents was found to be the wild type, which is an autosomal dominant inheritance. The new genetic variant has not been previously reported in the ClinVar and HGMD databases and the Genome Aggregation Database (gnomAD). Conclusion: This is the first incidence of Weiss-Kruszka syndrome relating to the nonsense variant in the ZNF462 gene in China. The finding from this study is novel in its expansion the variant spectrum of the ZNF462 gene and clarifies the genetic aetiology of the patient and his father.